2017
DOI: 10.1111/crj.12725
|View full text |Cite
|
Sign up to set email alerts
|

Tailored intraoperative localization of non‐palpable pulmonary lesions for thoracoscopic wedge resection using hybrid room technology

Abstract: Our experience confirms that HOR is suitable for simultaneous localization and VATS resection of 'difficult' pulmonary lesions. A versatile approach, using different devices, seems advisable for the removal of targets in every clinical scenario, reducing the VATS conversion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Stanzi et al reported encouraging results in terms of successful localization using both hookwires and coils, effectiveness of VATS procedures (only 1 conversion to thoracotomy out of 11 iVATS), overall procedural time, complication rates (no pneumothorax, no wire dislodgement) and radiation exposure using HOR and iVATS for non-palpable lung nodules (31).…”
Section: Discussionmentioning
confidence: 99%
“…Stanzi et al reported encouraging results in terms of successful localization using both hookwires and coils, effectiveness of VATS procedures (only 1 conversion to thoracotomy out of 11 iVATS), overall procedural time, complication rates (no pneumothorax, no wire dislodgement) and radiation exposure using HOR and iVATS for non-palpable lung nodules (31).…”
Section: Discussionmentioning
confidence: 99%
“…Lipiodol has been reported to have favorable factors include less diffusion and long presentation (even greater than three months) but there is a risk of causing allergies and embolism if this contrast agent accidentally reached the systemic circulation. 14 In addition, the CT-G localization methods have common deficiencies, [15][16][17] such as physical discomfort, psychological stress, ionizing radiation exposure, occupying radiology resources and increasing the burden of logistics department. Virtual-assisted lung mapping (VAL-MAP) is a preoperative bronchoscopic multispot dye-marking technique using virtual images.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported detailed patient positioning and CBCT acquisition protocols. 16 CBCT images were jointly reviewed by radiologistsandsurgeonstoconfirmthepresenceofthetargetlesion and to plan the needle trajectory for the percutaneous placement of the metallic marker. The trajectory (Fig.…”
Section: Ivats Procedural Workflowmentioning
confidence: 99%
“…An extended delay in surgery after localization may result in an increased risk of complications, such as pneumothorax or marker dislodgement. 15 Wepreviouslyreportedourworkflowforsingle-stageintraoperative localization and thoracoscopic removal of nonpalpable pulmonary nodules in HOR, 16 based on the alternative use of 2 different types of metallic markers, depending on target characteristics. The aim of the present study is to evaluate the localization yield of iVATS wedge resection in a larger cohort of consecutive patients with nonpalpable pulmonary nodules.…”
Section: Introductionmentioning
confidence: 99%